Monumental art: Visual and cultural analysis - Ali Salman Aldwairi, Issam; Abdel Qader Suliman Bani Milhem, Osamah; Mohammad Ali Ayesh, Saleem; Hasan Jamil Barqawi, Manal (project baikal, 2025)
Human societies naturally give rise to memorial art, which reflects regional geography and values. This study examines the role of memorials in enhancing environmental aesthetics and increasing public awareness, with a focus on sculptures that incorporate Arabic script. Its importance comes from highlighting the memorial's design, materials, and artistic impact on viewers' intellectual and emotional perception to create captivating outdoor spaces and go beyond traditional indoor murals.
Keywords: visual reading; memorial; abstract; Arabic calligraphy